Métodos heurísticos aplicados ao problema da árvore de Steiner rectilinear - Silva, Thiago Gouveia da (2009)
This work presents a new heuristic, called Heurística 1, and the implementations of the GRASP, Simulated Annealing and Genetic Algorithms metaheuristics for the rectilinear Steiner minimum tree problem (RSMTP), talking about its theoretical aspects, like computational complexity, and practical ones, like pseudo-codes and implementation strategies. The new techniques for RSMTP presented, especially the Genetic Algorithms, have computational results of superior quality in comparison to the best heuristics in present litera